ANALISIS PENGARUH JUMLAH PRODUKSI, HARGA BERAS LOKAL, DAN KONSUMSI BERAS TERHADAP IMPOR BERAS DI PROVINSI JAWA TENGAH (2010 – 2014) - Yasinta Putri Dewi; Riyadi Riyadi; Fatchun Hasyim (Politeknik Negeri Semarang, 2016)
Central Java is a province that has a prosperous land and appropriate to for crops. This research aims to analyze the influence of Production, Domestic Price, and Rice Consumption in Central Java toward Import Volume of Rice in Central Java. The data that are used were secondary data during period 2010 – 2014, which were analyzed using multiple regression analysis to estimate the influential factors. According to data analysis report it shows that Production, Domestic Price, and Rice Consumption simultaneously had significant influence toward Import Volume of Rice in Central Java. Nevertheless, partially only Domestic Price, and Rice Consumption in Central Java that has significant influence toward Import Volume of Rice in Central Java. While the Determination Coefficient (Adjusted R2) = 0.584 or 58.4%, it means that the Import Volume of Rice in Central Java was 58.4% which was explained by Production, Domestic Price, and Rice Consumption in Central Java, and the rest of 41.6% were affected by any other factors outside the models. The conclusion is the researcher can develop of factors affecting Import Volume of Rice in Central Java, such as inflation, exchange rate, gross regional domestic bruto, etc.